The watchdog still barks : how accountability reporting evolved for the digital age - Knobel, Beth (Donald Mcgannon Communication Research Center's Everett C. Parker Book Ser., 2018)
Perhaps no function of the press is as important as being a watchdog over the government. Based on the first content analysis to focus specifically on accountability journalism nationally, this book shows how American newspapers held fast to the watchdog role in the digital age, despite financial and technological challenges.